Paley–Wiener–Schwartz type theorem for the wavelet transform. Issue 7 (19th May 2019) - Pathak, R. S.; Singh, Abhishek
ABSTRACT: In the present paper, we discuss about extension of the wavelet transform on distribution space of compact support and develop the Paley–Wiener–Schwartz type theorem for the wavelet transform on the same. Furthermore, Paley–Wiener–Schwartz type theorem for the wavelet transform is also established using the relation between the wavelet transform and double Fourier transform.